2019
DOI: 10.1111/are.14262
|View full text |Cite
|
Sign up to set email alerts
|

Potential involvement of a DMRT family member ( Mr‐Dsx ) in the regulation of sexual differentiation and moulting in the giant river prawn Macrobrachium rosenbergii

Abstract: Macrobrachium rosenbergii is an important aquaculture species known as the king of freshwater prawn. Macrobrachium rosenbergii displays remarkable sexual dimorphism, yet our knowledge of the molecular mechanism underpinning sex determination and differentiation of M. rosenbergii is still fragmentary. In this study, through in silico prediction and experimental characterization, we identified a new Dmrt gene (Mr-Dsx) from M. rosenbergii. The cDNA of Mr-Dsx included a 115 bp 5′ untranslated region (UTR), a 2,568… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 56 publications
(94 reference statements)
0
27
0
Order By: Relevance
“…Even in isopods, in which an elevated bacterial dosage of Wolbachia resulted in feminization, it was postulated that Wolbachia feminized males through intervention in the IAGswitch by instigating dysfunctional insulin receptors (Herran et al, 2020). However, while few other genes were found to be associated with the expression of IAG [MIH, GIH, CHH, CFSH, DMRT, and GEM (Li et al, 2015;Jin et al, 2019;Zhong et al, 2019;Jiang et al, 2020)], genes (other than the IAG itself) that act directly within the core of the IAG-switch cascade, have yet to be found.…”
Section: Introductionmentioning
confidence: 99%
“…Even in isopods, in which an elevated bacterial dosage of Wolbachia resulted in feminization, it was postulated that Wolbachia feminized males through intervention in the IAGswitch by instigating dysfunctional insulin receptors (Herran et al, 2020). However, while few other genes were found to be associated with the expression of IAG [MIH, GIH, CHH, CFSH, DMRT, and GEM (Li et al, 2015;Jin et al, 2019;Zhong et al, 2019;Jiang et al, 2020)], genes (other than the IAG itself) that act directly within the core of the IAG-switch cascade, have yet to be found.…”
Section: Introductionmentioning
confidence: 99%
“…This review serves as an outline reference for endocrine-driven sex determination and/or sexual differentiation systems in Malacostraca and Branchiopoda crustaceans. Although the transcriptional regulatory mechanisms between IAG and Dmrt genes have been investigated by gene knockdown approaches [ 161 , 162 ], the eyestalk (XO-SG complex)-derived neuropeptides that regulate IAG expression and those molecular networks are still largely unknown. Moreover, even among Malacostraca species, previous findings have so far demonstrated that endocrine systems vary in certain respects such as heterodimeric disulfide bond patterns of IAG.…”
Section: Discussionmentioning
confidence: 99%
“…The insulin-like androgenic gland hormone (IAG) secreted from androgenic gland (AG) is a key regulator in sexual differentiation. Recent studies have shown that IAG itself is controlled by several genes and hormonal factors (Shen et al, 2014;Shi L. et al, 2019;Zhong et al, 2019). The detailed mechanisms and the role of sex-related genes and miRNAs in the IAG regulation are discussed in detail in other sections of the present review.…”
Section: Sexual Differentiation and Maturationmentioning
confidence: 91%
“…The Dmrt gene family plays essential roles in sexual differentiation. This gene family has been widely studied in vertebrates, nematodes, and insects, however, limited information is available regarding the molecular function of the Dmrt gene family in decapods (Zhong et al, 2019). To date, Dmrt has been isolated from different crustacean species including E. sinensis (Zhang and Qiu, 2010), the water flea D. magna (Toyota et al, 2013), S. verreauxi (Chandler et al, 2015), F. chinensis (Li et al, 2012b)…”
Section: Dmrt Gene Familymentioning
confidence: 99%
See 1 more Smart Citation